REGULASI GENETIK PADA PERKEMBANGAN TUMBUHAN - Wandari, Rifa Dwi; Wan Syafi’i (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Genetic regulation of plant development involves a complex network of transcription factors, microRNAs, epigenetic modifications, and hormonal signals that together determine growth patterns, differentiation, and environmental responses. This review synthesizes findings from five recent (2019–2025) journal articles highlighting roles of key transcription factors, miRNAs, epigenetic mechanisms, and hormonal interplay in controlling root, leaf, and vegetative-to-reproductive transitions. We performed a systematic literature search on databases (PubMed, Web of Science, Google Scholar) using targeted keywords and selected five representative reviews and studies. Results indicate multilayered integration: (1) transcription factors act as central regulatory nodes; (2) miRNAs fine-tune developmental transitions by regulating target transcripts; (3) epigenetic marks set dynamic chromatin states; and (4) hormone crosstalk aligns environmental cues with genetic programs. CRISPR-based genome editing provides tools for functional dissection and crop improvement. In conclusion, an integrative understanding of genetic regulation offers pathways for targeted interventions to develop more adaptive, productive plant varieties.